2014
DOI: 10.1016/j.bbamcr.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Take five — Type VII secretion systems of Mycobacteria

Abstract: Mycobacteria use type VII secretion (T7S) systems to secrete proteins across their complex cell envelope. Pathogenic mycobacteria, such as the notorious pathogen Mycobacterium tuberculosis, have up to five of these secretion systems, named ESX-1 to ESX-5. At least three of these secretion systems are essential for mycobacterial virulence and/or viability. Elucidating T7S is therefore essential to understand the success of M. tuberculosis and other pathogenic mycobacteria as pathogens, and could be instrumental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
161
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 88 publications
3
161
0
3
Order By: Relevance
“…ESX-1 is partially missing in the vaccine strain Mycobacterium bovis Bacille Calmette-Guérin [32], indicating a contribution to virulence. Previous investigations have demonstrated a crucial role of T7SS in bacterial survival within the host [21,23,31,32], consistent with transmission electron micrographs of interactions between S. iniae DX09 and spleen cells from diseased catfish. Moreover, considerable evidence is available supporting essential roles of the actinobacterial ESS protein secretion system in virulence [26][27][28][29].…”
Section: Iusa1 and Sf1supporting
confidence: 52%
See 2 more Smart Citations
“…ESX-1 is partially missing in the vaccine strain Mycobacterium bovis Bacille Calmette-Guérin [32], indicating a contribution to virulence. Previous investigations have demonstrated a crucial role of T7SS in bacterial survival within the host [21,23,31,32], consistent with transmission electron micrographs of interactions between S. iniae DX09 and spleen cells from diseased catfish. Moreover, considerable evidence is available supporting essential roles of the actinobacterial ESS protein secretion system in virulence [26][27][28][29].…”
Section: Iusa1 and Sf1supporting
confidence: 52%
“…Pathogenic mycobacteria generally possess up to five different T7SS (ESX-1, ESX-2, ESX-3, ESX-4 and ESX-5), which have possibly evolved via gene duplication [31]. Several studies suggest that ESX-1, the first T7SS identified, strongly influences host-pathogen interactions, in particular, the ability of bacteria to escape the phago-vacuole of infected cells (macrophages and dendritic cells) [23]. ESX-1 is partially missing in the vaccine strain Mycobacterium bovis Bacille Calmette-Guérin [32], indicating a contribution to virulence.…”
Section: Iusa1 and Sf1mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the only known secretion systems capable of translocating proteins across both M. tuberculosis membranes are the type VII secretion systems encoded by esx operons. Although inner membrane proteins of ESX secretion systems have been characterized (16), channel proteins that are required for protein translocation across the outer membrane are currently unknown in M. tuberculosis. We hypothesized that deletion or inactivation of outer membrane channel proteins in M. tuberculosis may result in increased antibiotic resistance, as has been described for Gram-negative bacteria and Mycobacterium smegmatis (17,18).…”
mentioning
confidence: 99%
“…Along with additional species/lineage-specific factors, such as the mycobacterial PE and PPE proteins, these components have been proposed to assemble in the plasma membrane, where they translocate specific protein substrates to the cell surface (or to the periplasmic space of mycobacteria) (figure 4B of ref. 18). The Mtb genome encodes five distinct but evolutionarily related type VII/ESX systems (ESX-1 to ESX-5) at different loci around the genome, and the primary attenuating mutation in the Mycobacterium bovis bacillus Calmette-Guérin vaccine strain is a deletion of a large segment of the ESX-1 locus (19).…”
mentioning
confidence: 99%